Hubungan antara Tabungan dan Pertumbuhan Ekonomi di Indonesia: Penerapan Uji Kausalitas Toda-Yamamoto - Prihadyatama, Ardila (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
The debate between two opposing theories of growth continues to this day. Loyalist opinion of the Solow Growth Theory which states that higher savings precede and cause higher economic growth. In the opposite camp, there is another growth theory that is no less powerful than that proposed by Keynes. Supporters of this theory have the view that growth in output (or income) causes growth in savings. Proponents of this theory argue that an increase in output will lead to an increase in income, thereby increasing the level of savings in the economy. This research aims to investigate the causality between savings and economic growth in Indonesia. The data used in this research is time series data from Saving, FDI (Foreign Direct Investment) and GDP (real Gross Domestic Product) in Indonesia from 1981 to 2020. All data was obtained by accessing the official website of the International Monetary Fund. The research method used is Toda Yamamoto causality testing. Indonesia tends to agree with the theory presented by Keynes that in Indonesia the savings rate is influenced by GDP and FDI.